Washington Avenue with walking visitors, near the Manufacturers, King County Buildings and Machinery Hall, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Dobbs, Beverly Bennett (1909)
Beverly Bennett Dobbs was born in 1868 near Marshall, Missouri. In 1888 Dobbs moved to Bellingham, Washington and operated a photography studio there for 12 years. In 1900 Dobbs moved to Nome, Alaska and continued to work as a photographer capturing images of Nome, the Seward Peninsula and Inuit people. In 1909, Dobbs started the Dobbs Alaska Moving Picture Co. and began making films about the Gold Rush. By 1914, Dobbs had moved back to Seattle and was creating more films through the Dobbs Totem Film Company which he ran until his death in 1937. PH Coll 755.2 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number